Low-wage careers: are there dead-end firms and dead-end jobs? - Alexander Mosthaf; Claus Schnabel; Jens Stephani (Institute for the Study of Labor (IZA), 2010)
Using representative linked employer-employee data of the German Federal Employment Agency, this paper shows that just one out of seven full-time employees who earned low wages (i.e. less than two-thirds of the median wage) in 1998/99 was able to earn wages above the low-wage threshold in 2003. Bivariate probit estimations with endogenous selection indicate that upward wage mobility is higher for younger and better qualified low-wage earners, whereas women are substantially less successful. We show that the characteristics of the employing firm also matter for low-wage earners' probability of escaping low-paid work. In particular small plants and plants with a high share of low-wage earners often seem to be dead ends for low-wage earners. The likelihood of leaving the low-wage sector is also low when staying in unskilled and skilled service occupations and in unskilled commercial and administrational occupations. Consequently, leaving these dead-end plants and occupations appears to be an important instrument for achieving wages above the low-wage threshold.
Keywords: J30; J60; 330; Low-wage employment; wage mobility; Germany; Niedriglohn; Erwerbsverlauf; Soziale Mobilität; Deutschland